METODE TEAMS GAMES TOURNAMENST (TGT) UNTUK MENINGKATKAN KEMAMPUAN MENULIS PUISI BEBAS SISWA KELAS V-B SDN CILEUKSA - Asyifa, Nisa Fuji; Sunarya, Dede Tatang; Djuanda, Dadan (Jurnal Pena Ilmiah, 2017)
The purpose of this classroom action research (using spiral model by Kemmis and Taggart) was to improve learning process (including teacher activity and student activity) and learning result of free verse writing by applying Teams Games Tournaments method. The subject were 5th-B grade Cileuksa Elementary School Paseh Subdistric Sumedang Regency. Students struggles by decided an idea, and free verse writing with personification and simile figuartive language. The research was doing up to three cycles with learning process result was increasing in every cycles until reached the target. The learning result, it was also increasing in every cycles and reached the target. First cycles reached 26,9%, second cycles reached 73,91%, and third cycles reached 86,95%. The analizet data was qualitative data, enhanced with free verse writing test evaluation. Result found that application of Teams Games Tournaments method improved students free versewriting skills.